Resposta :
Resposta:
[tex]4x ^ { 2 } -2x+1=0 \\ x=\frac{-\left(-2\right)±\sqrt{\left(-2\right)^{2}-4\times 4}}{2\times 4} \\ x=\frac{-\left(-2\right)±\sqrt{4-4\times 4}}{2\times 4} \\ x=\frac{-\left(-2\right)±\sqrt{4-16}}{2\times 4} \\ x=\frac{-\left(-2\right)±\sqrt{-12}}{2\times 4} \\ x=\frac{-\left(-2\right)±2\sqrt{3}i}{2\times 4} \\ x=\frac{2±2\sqrt{3}i}{2\times 4} \\ x=\frac{2+2\sqrt{3}i}{8} \\ x=\frac{1+\sqrt{3}i}{4} \\ x=\frac{-2\sqrt{3}i+2}{8} \\ x=\frac{-\sqrt{3}i+1}{4} \\ x=\frac{1+\sqrt{3}i}{4} \\ x=\frac{-\sqrt{3}i+1}{4} [/tex]